Investigating Mechanisms of Nanotoxicity of a Next-Generation Lithium Cobalt Oxide Nanomaterial - (:unkn) unknown (My University, 2021)
Commercial use of engineered nanomaterials (ENMs; materials in the range of 1-100 nm) has grown dramatically since the discovery of the means to observe, characterize, and controllably synthesize these materials at the end of the 20th century. Today, ENMs represent a global market valued in the trillions of dollars, incorporated into products because of the unique properties they confer, including increased strength, catalytic activity, and interactions with light. In this time, ENMs have also grown from relatively simple first-generation materials, such as Au, Ag, and carbon ENMs, to complex next-generation materials incorporating numerous elements into materials with complex secondary structures, such as the lithium intercalating complex metal oxide cathode materials used in lithium-ion batteries (LIBs). The commercial use of ENMs results in ENM waste on the order of hundreds of thousands to millions of tons annually, enough that ENM waste represents an emerging environmental concern. LIB cathode waste alone amounts to hundreds of thousands of tons annually, with little of this recycled. As the development and use of ENMs has grown, alongside it has grown the field of nanotoxicology, determined to understand if the same properties, such as size, core material, surface area, and surface chemistry, that confer useful properties to ENMs also imbue them with toxicity toward biological systems. However, while the diversity of ENMs has grown, the field of nanotoxicology has focused to a large extent on examining the toxicity of first-generation materials (e.g., Au and Ag) and on oxidative stress as the mechanism of nanotoxicity. Oxidative stress as a mechanism of nanotoxicity is understood as a general mechanism of cellular damage by reactive oxygen species (ROS). However, simple observation of ROS is not explanatory of ENM toxicity, as ROS are not only damaging molecules, but are involved in regulation of critical cellular processes including metabolism, growth, and differentiation. Therefore, the presence of redox-sensitive components in these pathways makes them susceptible to specific interactions with redox-active ENMs or ROS even at sublethal, physiologically relevant concentrations. Environmental nanotoxicology has also focused to a large degree on the aquatic invertebrate Daphnia magna, whose wide use in the field of toxicology more generally makes it a broadly applicable model. However, D. magna reside in the water column, while many ENMs are expected to settle in the aquatic environment and concentrate in the sediment, making testing on sediment-dwelling organisms such as the invertebrate midge species Chironomus riparius important for understanding the potential environmental impacts of ENMs. Overcoming these limitations of nanotoxicology requires testing of next-generation ENMs, including on sediment-dwelling organisms, and the exploration of mechanisms of nanotoxicology at the molecular level, beyond simple oxidative stress. A useful framework to guide the elucidation of this molecular-level understanding is the adverse outcome pathway (AOP). In this framework, the interaction of a toxicant such as an ENM with a biological system is understood from the standpoint of a molecular interaction between the toxicant and a biological component (called the molecular initiating event; MIE), which results in a series of key events (KEs) that occur in the biological system in response to this impact, and ultimately causes an adverse outcome (AO) for the biological system, such as the death of an organism or cell. By using molecular tools to interrogate ENM impacts at each stage of this process, it is possible to trace observed AOs through their series of associated KEs and ultimately down to the specific MIE(s). This thesis sought to address the shortcomings of current nanotoxicology by using molecular methods to inform an AOP for the toxicity of the next-generation complex metal oxide LIB cathode material lithium cobalt oxide (LCO) in sediment-dwelling Chironomus riparius and in Daphnia magna. Results of these investigations demonstrate oxidation of the Fe-S center of energy metabolism enzyme aconitase as an MIE of LCO toxicity, disrupted heme synthesis and energy metabolism as KEs by targeted and global gene expression analysis, KEs of altered metabolic gene expression and metabolite levels toward energy production by combined global gene expression and non-targeted metabolomics, and AOs of reduced growth and delayed development. This work thus demonstrates the paradigm by which ENM toxicity can be understood at the molecular level, including the interconnections of the MIE, KEs, and AOs for LCO within the AOP framework. Furthermore, this AOP, placed in the context of the literature, suggest a general AOP for toxicity of metal oxide ENMs in which the redox chemistry of a metal oxide ENM causes oxidation of redox-sensitive biological components, such as proteins and cofactors involved in energy metabolism, disrupting critical processes including energy metabolism, and ultimately disrupting growth and development at the organism level. Further exploration of the details of this AOP represent an exciting future direction for the investigation of the interaction of metal oxide ENMs with biological systems.
Keywords: Adverse outcome pathway; Chironomid; Daphnia; Lithium ion battery; Nanomaterial; Nanotoxicology